Development of a Whey Protein Hydrogel as an Alternative for the Microencapsulation of Calyx Extracts from Hibiscus sabdariffa - Ubaldo Richard Marin Castro; María del Pilar Ortiz Vignon; José Carlos Castillo Barrientos; Héctor Emiliano Morales Alayón; Cesar Antonio Ortiz Sánchez; Enrique Flores Andrade; Marisol Castillo Morales (Biology and Life Sciences Forum)
In the present study, a whey protein-based hydrogel was developed as an alternative for the microencapsulation of Hibiscus extracts. The resulting hydrogels showed a high percentage of moisture and water activity, along with a partial degradation of anthocyanins during their production and storage. The hydrogels exhibited particle sizes between 8 and 15 μm and retained some of the characteristic color properties of extracts. The results obtained provide a novel alternative for the microencapsulation of bioactive compounds through the use of protein-based carrier systems, highlighting their potential for the development of innovative encapsulation systems.